The Application of Titulus Finalis, Subscriptions, Total Stichometry in the Textual Classification of Early Printed Cyrillic Liturgical Tetraevangelia - Jerzy Ostapczuk (The Biblical Annals, 2025)
Subscriptions and final numerical notations are assumed to be the most succinct text entities in Greek and Church Slavonic Tetraevangelia. Their complex history was widely disregarded in these two traditions. T. Wasserman, along with his colleagues, has recently developed a new typology of subscriptions in Greek codices. The present study attempts to apply this new typological classification of subscriptions, based on their content, wording and gradual development, in a classification of Early Printed Cyrillic liturgical Tetraevangelia. All the Cyrillic Gospel editions issued in the 16th–18th centuries have been successfully divided into two main groups and nine subgroups. This division agrees with the one based on textual classification of several Gospel fragments, some paratexts preceding each Gospel book and the menologion.